"I don't know" My Cancer Risk: Implications for Health Behavior Engagement. Issue 5 (2nd March 2016) - Waters, Erika A.; Kiviniemi, Marc T.; Orom, Heather; Hay, Jennifer L.
Abstract: Background: Many people report uncertainty about their cancer risk. We examined whether such uncertainty was related to cancer prevention and detection behaviors. Methods: National Health Interview Survey data from 2005 to 2010 were analyzed. Participants reported their perceived risk for colorectal and breast cancers. Responses were coded as "valid" (i.e., less/as/more likely than average) or "don't know." Results: In bivariate analyses for both cancer sites and survey years, "don't know" responders (DKR) engaged in less physical activity than "valid" responders ( p < 0.05). DKR had lower mammography adherence than "valid" responders in 2005 and lower colorectal screening adherence in 2010 ( p < 0.05). DKR had marginally lower colorectal screening adherence and fruit/vegetable consumption in 2005 ( p < 0.06). Multivariable models indicated that the DKR–behavior relationship could be largely accounted for by education. Conclusion: Interventions that help people understand their cancer risk may provide particular benefit to people with low education and might consequently reduce health disparities.